2013
DOI: 10.4236/eng.2013.51b007
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Electrical Incidence Angle Modifiers of an Asymmetrical Photovoltaic/Thermal Compound Parabolic Concentrating-Collector

Abstract: Reflector edges, sharp acceptance angles and by-pass diodes introduce large variations in the electrical performance of asymmetrical concentrating photovoltaic/thermal modules over a short incidence angle interval. It is therefore important to quantify these impacts precisely. The impact on the electrical performance of the optical properties of an asymmetrical photovoltaic/thermal CPC-collector was measured in Maputo, Mozambique. The measurements were carried out with the focus on attaining a high resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…suns. The study demonstrated that the PV cell can still reach a high temperature even with a low concentration ratio, where the electrical efficiency was measured to be 20.9% at 25 °C [47]. The dependency of the electrical efficiency on the cell temperature is -0.4%/K, as illustrated in Fig.…”
Section: Number Of Cells In An Arraymentioning
confidence: 66%
See 1 more Smart Citation
“…suns. The study demonstrated that the PV cell can still reach a high temperature even with a low concentration ratio, where the electrical efficiency was measured to be 20.9% at 25 °C [47]. The dependency of the electrical efficiency on the cell temperature is -0.4%/K, as illustrated in Fig.…”
Section: Number Of Cells In An Arraymentioning
confidence: 66%
“…The experimental results of the different semiconductor materials are listed in Table 1. [46][47][48][49].…”
Section: Linear Concentrators: the Reflective Trough Of Low-medium Co...mentioning
confidence: 99%
“…The PVT Solarus collector belongs to the compound parabolic collector (CPC) type, which is commonly known as the maximum reflector concentrator (MaReCo) family [9], and it is widely described in the literature [10][11][12]. It is formed by a reflector with two asymmetrical truncated parabolic sections separated by a circular section (compound parabolic concentrator, CPC), a flat receiver with solar cells in both sides and bi-facial absorbers.…”
Section: B Solarus C-pv Collectormentioning
confidence: 99%
“…To reach to a new design that receives nearly as much as the flat collector, but at lower costs, will represent an upgrade. Three new geometries were proposed for lower latitudes 11 . Two of them present pure symmetric geometries (parabolic reflector and receivers symmetrically placed) and the third has a parabolic reflector but with an asymmetrically placed receiver as standard MaReCo (truncated CPC with a bifacial receiver plus parabolic and circular reflectors).…”
Section: B Solarus C-pv Collectormentioning
confidence: 99%
“…At peak hours, the measured efficiency was 20.9% per cell area and 13.9% per active glazed area. Several prototypes of the CPVT collector (with reflective/transparent end gables and different cell sizes) were further tested and compared [95], in order to minimize the impact of shading at oblique solar incidence angles. The measured results showed that, at large incident angles, the system with transparent end gables and larger cells performed better.…”
Section: Compound Parabolic Concentratormentioning
confidence: 99%